2013
DOI: 10.1371/journal.pone.0060980
|View full text |Cite
|
Sign up to set email alerts
|

CMS: A Web-Based System for Visualization and Analysis of Genome-Wide Methylation Data of Human Cancers

Abstract: BackgroundDNA methylation of promoter CpG islands is associated with gene suppression, and its unique genome-wide profiles have been linked to tumor progression. Coupled with high-throughput sequencing technologies, it can now efficiently determine genome-wide methylation profiles in cancer cells. Also, experimental and computational technologies make it possible to find the functional relationship between cancer-specific methylation patterns and their clinicopathological parameters.Methodology/Principal Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 25 publications
(22 reference statements)
1
43
0
Order By: Relevance
“…These clusters were reported in both ER + and ER -breast cancer tumors. Other investigators used a quantitative approach based on statistical methods and machine learning algorithms to quantify methylation differences in cases and controls and identify differentially methylated regions from genome-wide methylation profiles [140,141]. To elucidate the role of estrogen in the coordinated repression of gene clusters located at 16p11.2 in breast cancer, the concept of long-range epigenetic silencing (LRES) was studied.…”
Section: • Breast Cancermentioning
confidence: 99%
“…These clusters were reported in both ER + and ER -breast cancer tumors. Other investigators used a quantitative approach based on statistical methods and machine learning algorithms to quantify methylation differences in cases and controls and identify differentially methylated regions from genome-wide methylation profiles [140,141]. To elucidate the role of estrogen in the coordinated repression of gene clusters located at 16p11.2 in breast cancer, the concept of long-range epigenetic silencing (LRES) was studied.…”
Section: • Breast Cancermentioning
confidence: 99%
“…Graph theory model is built, but also to grasp the method of model transformation. Such as the example shown in the figure one, the model can be expressed as the follows [8].…”
Section: The Graph Theory Modelmentioning
confidence: 99%
“…We performed comprehensive comparison analyses of DNA methylation profiling in normal controls and breast cancers, which were downloaded from the Cancer Methylome System (CMS) (Gu et al 2013). Pair-wise comparison of average genome-wide methylation intensity across all breast cancers and normal cohorts showed that normal and breast cancer samples correlated reasonably well within classes, but not inter-classes ( Figure 1A).…”
Section: Global Differences Of Dna Methylation In Breast Cancermentioning
confidence: 99%
“…The genome-wide DNA methylation profiles from the Cancer Methylome System (CMS, http://cbbiweb.uthscsa.edu/KMethylomes) were used in the current study (Gu et al 2013). …”
Section: Genome-wide Dna Methylation Profilesmentioning
confidence: 99%
See 1 more Smart Citation